2006
DOI: 10.1161/01.atv.0000215001.92941.6c
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular Adhesion Molecule-1 Is Upregulated in Ischemic Muscle, Which Mediates Trafficking of Endothelial Progenitor Cells

Abstract: Background-Trafficking of transplanted endothelial progenitor cells (EPCs) to an ischemic organ is a critical step in neovascularization. This study was performed to elucidate the molecular mechanism of EPC trafficking in terms of adhesion molecules. Methods and Results-Using murine hindlimb ischemia model, we examined expressions of E-selectin, intercellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1 (VCAM-1), and platelet-endothelial cell adhesion molecule-1 (PECAM-1) in ischemic muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 30 publications
8
74
0
2
Order By: Relevance
“…Despite the lack of effect of DMOG-treated cells alone, the combination of IV DMOGtreated BMDACs and IM AdCA5 induced functional recovery and limb salvage in old mice, in which angiogenic responses are impaired as compared to young mice (4, 16), thus more closely resembling patients with critical limb ischemia. Finally, in addition to the synergistic therapeutic effects of IM AdCA5 and IV DMOG-treated BMDACs, stable retention of BMDACs in ischemic tissue is further aided by hypoxia-induced expression in vascular endothelial cells of ICAM-1 and E-selectin, which are known to interact with ␤ 2 integrins, and were recently shown to be involved in BMDAC homing to ischemic myocardium (35) and muscle (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lack of effect of DMOG-treated cells alone, the combination of IV DMOGtreated BMDACs and IM AdCA5 induced functional recovery and limb salvage in old mice, in which angiogenic responses are impaired as compared to young mice (4, 16), thus more closely resembling patients with critical limb ischemia. Finally, in addition to the synergistic therapeutic effects of IM AdCA5 and IV DMOG-treated BMDACs, stable retention of BMDACs in ischemic tissue is further aided by hypoxia-induced expression in vascular endothelial cells of ICAM-1 and E-selectin, which are known to interact with ␤ 2 integrins, and were recently shown to be involved in BMDAC homing to ischemic myocardium (35) and muscle (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Recently it was demonstrated that recruitment of CD34ϩ hematopoietic stem cells, the parent population of CD133ϩ EPCs, into the neovasculature of tumors utilizes the VCAM-1/ VLA-4 adhesive system (38). EPCs are recruited to ischemia-damaged muscle to reconstitute a functional microcirculation (32), and ICAM-1 plays a primary role in EPC recruitment to muscle (39). Ours is the first study to define the specific participation of the VCAM-1/ VLA-4 system, but not the ICAM/␤2 integrin subunit pair, in mediating EPC interactions with synovial cells.…”
Section: Discussionmentioning
confidence: 99%
“…[47]) with only one report (where reoxygenation was permitted after neutrophil isolation) finding no difference [44]. Although reports of modulation of ICAM-1 expression by hypoxia are conflicting [48,49], several studies have shown increased neutrophil adhesion to the endothelium under hypoxia (e.g. Ref.…”
Section: Adhesion Transmigration Chemotaxis and Recruitmentmentioning
confidence: 99%